(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
A taxonomic study on some orb-weaving spiders of the genus Cyrtarachne Thorell, 1868 (Araneae: Araneidae) were carried out from different areas of Bangladesh. Two species were identified in this study namely C. biswajiti n. sp. and C. sundari Tikader. C. biswajiti has described as new to science. Illustrated descriptions of the species were provided herewith. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 75-82